LEVEL OF COMMUNITY KNOWLEDGE ABOUT THE USE OF VITAMIN C AS A PREVENTION OF COVID-19 IN X URBAN VILLAGE, CITY OF TANGERANG SELATAN - Bebimilla, Kinta (SOCIAL CLINICAL PHARMACY INDONESIA JOURNAL, 2022)
In 2020, the COVID-19 pandemic continues to spread throughout the world, inclunding in Indonesia. Facing a situasuin like this, its is necessary to control and prevent COVID-19. One of them is by consuming vitamin C. Vitamin C is one of the recommended ways to increase the immune systkem or immune system in the midst of the COVID-19 pandemic This study aims to describe the level of public knowledge on the use of vitamin C as an effort to prevent COVID-19 in X Urban Village, South Tangerang City. The research method used is descriptive research with a cross sectional approach. The sampling techniques used in this research is probability sampling with simple random sampling method. The reseult of the research is that the characteristics of respondents are dominated by female respondents by 66% and most of them are dominated by the age of 21-30 years by 65%. The total number of respondentrs who work is 77,8% and has the latest education level of Diploma S1/S2/S3 by 48%. The level of good knowledge is dominated by female respondents by 76.08%, respondents with an age range of 21-30 years by 78.85%, respondents who work at 77.81% and respondents with the latest education Diploma S1/S2/S3 amounting to 77,44%. The level of knowledge of the respondents as a whole is at a fairly good level of 75%. The conclusion obtained in this study is that the level of public knowledge about the use of vitamin C as an effort to prevent COVID-19 in X Urban Village, South Tangerang City is at a fairly good level.